Validity of calculating continuous relative phase during cycling from measures taken with skin-mounted electro-goniometers - Whittle, C.; Jobson, S. A.; Smith, N. (Sensors, 2022)
The aim of this study was to assess the validity of electro-goniometers as a tool for recording continuous relative phase data at two joint couplings during cycling tasks at a range of cadences. Seven participants (4 male, 3 female, age: 29 ± 7 years, height: 1.76 ± 0.10 m, mass: 71.97 ± 11.57 kg) performed exercise bouts of 30 s at four prescribed cadences (60, 80, 100, 120 rev/min) on a stationary ergometer (Wattbike, Nottingham, UK). Measures were synchronously recorded by bi-axial electro-goniometers (Biometrics, UK) and a 12-camera motion-capture system (Qualisys, Gothenburg, Sweden), with both systems sampling at 500 Hz. Sagittal plane joint angle and joint angular velocity were recorded at the hip, knee and ankle and analysed for ten complete pedal revolutions per participant per condition. Data were interpolated to 100 time points and used to calculate mean continuous relative phase (CRP) per pedal revolution at two intra-limb couplings: (i) knee flexion/extension-ankle plantarflexion/dorsiflexion (KA) and (ii) hip flexion/extension-knee flexion/extension (HK). At the KA coupling, significant differences in mean CRP were found between measurement systems at 120 rev/min (p = 0.006). At the HK coupling, significant differences in mean CRP were found between measurement systems at 80 rev/min (p = 0.043) and 100 rev/min (p = 0.028). ICC values for most comparisons were below 0.5, suggesting poor levels of agreement between systems. Significant differences in mean CRP per pedal revolution and poor levels of agreement between systems suggests that electro-goniometers are not a suitable alternative to motion-capture systems when attempting to record CRP during cycling.